Paul as Apostle, Theologian, and Missionary in Ellen G. White’s Writings - Chrissutianto, Donny (Klabat Theological Review, 2021)
Among the apostles, Ellen G. White wrote a biography of Paul only, Sketches From the Life of Paul (1883). In addition of this book, there are numerous statements about him throughout her writings. The purpose of this paper is to see what the idea of White about Paul as an apostle, theologian, and missionary was. This research argues that White understood the office of Paul as apostle was closely related to his eagerness in studying the Word of God, delivering the message in its simplicity to the hearers (theologian) and his zealous for missionary work. These three are intertwined in the life of Paul after his conversion. As he was called to be an apostle, this office required him to share the truth to others as well as a shepherd for God’s people, nurturing them and protecting the church from the false teaching. The last task was closely related to his ability as theologian. She regarded him as a missionary. She stated that to be a missionary he was to teach the truth (theologian), to expand the church and to organize people to advance God’s work. Thus, these three roles interwove in Paul’s ministry. Keywords: Paul